Sports Injury and Sport Safety Practices among Undergraduate Sports Participants: Sports Injury and Safety among Undergraduate Sports - Bibi, Kainat; Kazmi, Muhammad Taqi; Baig, Muhammad Jawwad; Faraz, Aiman; Alqhtani, Raee S (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2025)
Sports participation among university students offers physical and psychological benefits but also poses a risk of injuries. Limited adherence to safety measures further increases vulnerability, particularly in contact and high-intensity sports. Objectives: To determine the prevalence of sports injuries and safety practices among undergraduate sports participants. Methods: This cross-sectional study was conducted on 377 male and female at different universities in Karachi using a self-administered questionnaire. Ethical approval was obtained, and consent forms were filled out by participants. SPSS version 22 was used to analyze data and calculate frequencies and percentages. Results: Among 377 participants, 59.2% were male and 40.8% female, aged 18–25 years. A majority (51.2%) reported injuries, with the hand (10.6%) and muscles (9.8%) being most affected. Only 41.6% reported using safety equipment, while 59.9% used none. Warm-up and cool-down routines were practiced by 70.8% and 61.5%, respectively. Conclusions: Sports injuries are common among undergraduate participants, while safety equipment use remains low despite awareness of warm-up and cool-down practices. Findings highlight the urgent need for universities to strengthen safety protocols and provide education on injury prevention to safeguard student-athletes.